Biomechanical compensation mechanisms during stair climbing – The effect of leg length inequalities - Siebers, Hannah Lena; Eschweiler, Joerg; Michalik, Roman; Migliorini, Filippo; Tingart, Markus; Betsch, Marcel (Gait & Posture, 2022)
Background: Stair climbing is a complex and demanding daily activity with increased physical loads. Therefore, analyzing stair climbing abilities is a frequently used diagnostic tool. Leg length inequalities (LLIs) are a common condition in the population, with individual consequences like lower back pain, scoliosis, and osteoarthritis. Despite its high prevalence, the necessary treatment, for mild LLIs, is still controversial. Previously, the focus was to analyze the effects of LLIs during static standing and walking. To create a holistic view on the dynamic effects of LLIs, and since climbing stairs produces a similar biomechanical imbalance as LLIs, the compensation mechanics during stair climbing are of special interest. Research question: What are the biomechanical compensation mechanisms of (simulated) LLIs during ascending and descending stairs? Methods: Thirty-five healthy participants were measured with the inertial measurement system MyoMotion during stair climbing with simulated LLIs of 0–3 cm. The maximum estimated lower limb joint angles of the long and short leg were analyzed with statistically repeated measurement models. Results: The long leg showed significantly increased hip and knee flexion, while the short leg showed decreased hip and knee flexion, decreased dorsiflexion, and significantly increased plantarflexion. Different mechanisms were found in the case of 1 cm LLI when compared to greater LLIs. In the former, increased hip and knee flexion in the short leg accompanied by increased dorsiflexion in the long leg was observed. In the latter, the dorsiflexion of the long leg was reduced. Significance: Except for the reduced dorsiflexion of the long leg (LLI >1 cm), during stair climbing compared compensation mechanisms as during walking were presented, with the long leg functionally shortened and the short leg lengthened. Although the feet were already on different levels, during stair climbing with the step-over-step technique, significant compensation mechanisms were found as a consequence of LLIs.
CRIS-Team Scopus Importer:2022-07-20
Keywords: IMU; Leg length differences; Leg length discrepancies; Stair climbing